IONESCU-IONESCO, VOIX D’UN EXILÉ ? PROPOSITION D’UNE RELECTURE THÉORIQUE - Iulian-Emil COȚOFANĂ (Studia Universitatis Babeş-Bolyai. Philologia, 2024)
Ionescu-Ionesco, Voice of an Exile? Proposal for a Theoretical Rereading. In this paper, we propose a different reading of Eugène Ionesco’s exile by drawing from a selection of texts from the 1930s and afterwards. As our purpose is to challenge the prevailing discourse surrounding the topic, we have opted to focus on critical and theoretical elements rather than biographical details. We keep in mind that the author’s contributions and the research on his work are two intertwined discourses. In post-1989 Romania, Ionesco is widely regarded as one of the leading literary figures of the Romanian exile. It is our opinion that his exiled status has not been sufficiently investigated, and our aim is to demonstrate that prudence and close reading could uncover some striking nuances that could lead scholars to the solution of a central question: Should Ionescu-Ionesco be regarded as an exile or rather as an expatriate?